Warm Quartz Sand Neck Pillow Therapy for Neck Muscle Pain in Pottery Porter Workers - I Gusti Agung Ayu Ulan Anggreyani; I Ketut Andika Priastana; Yohanes Zenriano Tarigan (Pubfine Media Group, 2026)
Introduction: Neck muscle pain is commonly associated with musculoskeletal disorders (MSDs) and represents one of the most frequent complaints among manual labor workers. This condition is largely influenced by occupational factors, particularly repetitive activities, heavy physical workload, and non-ergonomic working postures. Non-pharmacological interventions are increasingly recommended as alternative and preventive strategies for managing work-related musculoskeletal pain. This study aimed to determine the effect of warm quartz sand neck pillow therapy on neck muscle pain among pottery porter workers at CV Puspa Jembrana. Methods: This study employed a pre-experimental design using a one-group pretest–posttest approach. The study population consisted of 90 active workers at CV Puspa Jembrana. A total of 81 participants were selected using quota sampling. Neck pain intensity was measured before and after the intervention, and data were analyzed using the Wilcoxon Signed Rank Test. Results: The findings demonstrated a statistically significant difference in neck muscle pain intensity before and after the intervention (p = 0.001), indicating a reduction in pain following the application of warm quartz sand neck pillow therapy. Conclusion: Warm quartz sand neck pillow therapy has a significant effect in reducing neck muscle pain among pottery porter workers. This intervention may serve as an effective non-pharmacological nursing strategy for managing work-related neck pain in manual labor populations.